Pioneering the Developmental Frontier - Larson, Elizabeth D. (Mol Cell, 2021)
Coordinated changes in gene expression allow for the single fertilized oocyte to develop into a complex, multi-cellular organism. These changes in expression are controlled by transcription factors that gain access to discrete cis-regulatory elements in the genome, allowing them to activate gene expression. While nucleosomes present barriers to transcription-factor occupancy, pioneer transcription factors have unique properties that allow them to bind DNA in the context of nucleosomes, define cis-regulatory elements and facilitate the subsequent binding of additional factors that determine gene expression. In this capacity, pioneer factors act at the top of gene regulatory networks to control developmental transitions. Nonetheless, developmental context also influences pioneer-factor binding and activity. Here we discuss the interplay between pioneer factors and development, both their role in driving developmental transitions and the influence that cellular environment has on pioneer-factor binding and activity.